2017
DOI: 10.1111/jog.13462
|View full text |Cite
|
Sign up to set email alerts
|

Chromium supplementation in women with polycystic ovary syndrome: Systematic review and meta‐analysis

Abstract: Aim: Increasing evidence has suggested that chromium supplementation may improve the clinical symptoms of polycystic ovary syndrome (PCOS), yet the results have been inconsistent. To derive a more precise estimation of the efficacy of chromium, a meta-analysis was performed. Methods: Studies published in PubMed, EMBASE and the Cochrane Library up to April 2017 were retrieved. Standardized mean differences (SMD) with 95%CI were calculated for net changes using random-effects or fixed-effects models. Results: A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 49 publications
0
9
0
1
Order By: Relevance
“…Meta-analysis inducted six randomized clinical trials with 351 PCOS women conducted by Tang et al indicates that chromium picolinate supplying has a positive effect in lowering insulin resistance but deleterious effect with regard to increasing total and free testosterone in these women. No significant improvement on hormone status, insulin metabolism and lipid profiles was observed [24]. The results are not sufficient for implementation of Cr III supplementation to the standard therapy in preventing and treating insulin resistance of women suffering from PCOS [25].…”
Section: Polycystic Ovary Syndromementioning
confidence: 78%
“…Meta-analysis inducted six randomized clinical trials with 351 PCOS women conducted by Tang et al indicates that chromium picolinate supplying has a positive effect in lowering insulin resistance but deleterious effect with regard to increasing total and free testosterone in these women. No significant improvement on hormone status, insulin metabolism and lipid profiles was observed [24]. The results are not sufficient for implementation of Cr III supplementation to the standard therapy in preventing and treating insulin resistance of women suffering from PCOS [25].…”
Section: Polycystic Ovary Syndromementioning
confidence: 78%
“…The rest of the studies of the application of therapy or supporting therapy of PCOS with Cr were conducted in mature women, and the meta-analysis of the results is presented in review studies [5255]. In Heshmati’s work [53], the final meta-analysis included only five properly randomised and placebo (or an approved drug)-controlled studies, with 137 women with PCOS in total.…”
Section: Resultsmentioning
confidence: 99%
“…Comparing Cr with metformin treatment, it was indicated that supplementation of diet with Cr was not related to insulin concentration [59, 60]. Meta-analysis conducted by Tang et al [55] indicates the improvement in insulin sensitivity; however, it has failed to show a beneficial effect of Cr supplementation on the level of total and free testosterone. Data analysis showed no effect of supplementation on body mass, fasting insulin and glucose or serum lipid levels.…”
Section: Resultsmentioning
confidence: 99%
“…Chromium is the basic element involved in the metabolism of carbohydrates and lipids; therefore, it has become one of the most commonly consumed dietary supplements in the USA [ 103 ]. The indications for its supplementation were once very broad; however, chrome is currently one of the most controversial components by which its influence is strongly undermined [ 104 , 105 ]. It was argued that it is not an essential micronutrient, but has potential benefits and/or side effects.…”
Section: Lifestyle Changesmentioning
confidence: 99%